Urticaria Multiforme in a Child: A Case Report - Isabele Oliveira Santos; Rafaela Carvalho Abrahão; Talita Caldas Oliveira; Paula Figueiredo Marsillac; Daniel Lago Obadia; Alexandre Carlos Gripp (Journal of the Portuguese Society of Dermatology and Venereology, 2020)
Urticaria multiforme is an acute hypersensitivity reaction which can be considered a morphological subtype of urticaria. It is more common in children and as its clinical presentation resembles other pathologies such as erythema multiforme, urticarial vasculitis and serum-sickness-like reaction, it has been often underdiagnosed. We report a case of a 1-year and 9-month-old child with exuberant skin lesions associated with systemic manifestations with complete and quick recovery after H1-antihistamines and iv steroids in an intensive care unit.